Mediating effect of self-efficacy on the relationship between Big Five personality and medication adherence in Chinese hypertensive patients: a national cross-sectional study - Du, Mingliang; Wu, Yibo; Wang, Boran; Jiang, Miao; Chen, Jiangyun; Hui, Hui (Frontiers in Psychology, 2024)
The study aims to evaluate personality characteristics, self-efficacy, and medication adherence in Chinese patients with hypertension, while also investigating how self-efficacy mediates the relationship between personality traits and medication adherence. Methods: This investigation included 787 Chinese patients diagnosed with hypertension, as reported in the "2021 China Family Health Index Survey Report." The study employed several assessment tools such as a General Information Questionnaire, the Brief Big Five Inventory (BFI-10), the New General Self-Efficacy Scale (NGSES), and the Medication Adherence Rating Scale (MARS). Statistical analyses encompassed the Mann-Whitney U test, chi-square test, multiple logistic regression, Spearman's rank correlation, standardized regression coefficients, and Bootstrap techniques. Results: 1) Individuals with debt, who also possess high levels of self-efficacy, tend to adhere more consistently to their medication regimens. 2) An analysis of personality traits indicated that Extroversion,Conscientiousness and Openness positively influences self-efficacy,while Agreeableness and Neuroticism negatively impacts it. 3) Self-efficacy plays a mediating role in the indirect relationship between personality traits such as Extroversion and neuroticism and medication adherence.In the context of Chinese adults, both self-efficacy and Extroversion positively influence medication adherence, whereas high levels of neuroticism adversely impact it. Furthermore, self-efficacy serves as a mediating factor in the linkage between personality traits and medication adherence.